The Enhanced Critical Incident Technique Investigation of Girls’ Perceptions of Prosocial Connectedness in a Wraparound Program - Barrett-Wallis, Rebecca; Goodwill , Alanaise (Canadian Journal of Counselling and Psychotherapy, 2020)
Women and girls are being implicated in gang-related operations at alarming rates. Anti-social gang behaviours such as drug trafficking, sexual exploitation, gun violence, and street entrenchment are of particular concern. British Columbia has seen a rise in gang-associated violence and homicide directed at or involving women over the last decade. Positive youth development initiatives such as the one in this study aim to support youth currently involved in or at risk of being involved in gangs. School personnel identify students who are exposed to anti-social gang behaviours and refer them to a wraparound program where they are matched with an adult mentor who works with them and their families to facilitate prosocial connections to five life domains: (a) school, (b) community, (c) home, (d) prosocial peers, and (e) the self. A 2012 evaluation report determined the program to be effective in reaching its objectives with a predominantly male population (84%). However, between 2015 and 2016, the program dramatically increased its responsiveness to girls, with a nearly 50% increase in female referrals. Using the enhanced critical incident technique (ECIT), the purpose of the study was to describe how female-identifying students articulate “prosocial connectedness” within the context of their experiences in a school-based wraparound gang prevention program. Critical incidents were collected by the first author, who interviewed eight girls and asked them the following: “What has helped/hindered/would have better helped facilitate your prosocial connectedness?” Findings were organized into 34 categories. ECIT analyses point to the effectiveness of using a relational/attachment model to inform strategies for gang prevention and school-based intervention in female youth.